Tracheostomy Outcomes in COVID-19 Patients in a Low Resource Setting. (November 2022) - Tang, Liyang; Kim, Celeste; Paik, Connie; West, Jonathan; Hasday, Steven; Su, Peiyi; Martinez, Eduardo; Zhou, Sheng; Clark, Bhavishya; O'Dell, Karla; Chambers, Tamara N.
Objectives: COVID-19 predominately affects safety net hospitals. Tracheostomies improve outcomes and decrease length of stay for COVID-19 patients. Our objectives are to determine if (1) COVID-19 tracheostomies have similar complication and mortality rates as non-COVID-19 tracheostomies and (2) to determine the effectiveness of our tracheostomy protocol at a safety net hospital. Methods: Patients who underwent tracheostomy at Los Angeles County Hospital between August 2009 and August 2020 were included. Demographics, SARS-CoV-2 status, body mass index (BMI), Charlson Co-morbidity Index (CCI), length of intubation, complication rates, decannulation rates, and 30-day all-cause mortality versus tracheostomy related mortality rates were all collected. Results: Thirty-eight patients with COVID-19 and 130 non-COVID-19 patients underwent tracheostomies. Both groups were predominately male with similar BMI and CCI, though the COVID-19 patients were more likely to be Hispanic and intubated for a longer time ( P  = .034 and P  < .0001, respectively). Both groups also had similar, low intraoperative complications at 2% to 3% and comparable long-term post-operative complications. However, COVID-19 patients had more perioperative complications within 7 days of surgery ( P  < .01). Specifically, they were more likely to have perioperative bleeding at their tracheostomy sites ( P  = .03) and long-term post-operative mucus plugging ( P  < .01). However, both groups had similar 30-day mortality rates. There were no incidences of COVID-19 transmission to healthcare workers. Conclusions: COVID-19 tracheostomies are safe for patients and healthcare workers. Careful attention should be paid to suctioning to prevent mucus plugging. Level of Evidence: 3